1993
DOI: 10.1152/ajpcell.1993.265.1.c122
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hepatocyte growth factor in growing and regenerating rat skeletal muscle

Abstract: The expression of hepatocyte growth factor (HGF) was studied in rat skeletal muscle during postnatal growth and during regeneration after ischemic injury. By Northern blot analysis two RNA transcripts with estimated sizes of 6.0 and 3.1 kb, respectively, could be detected in immature skeletal muscle at 2, 4, and 10 days after birth, whereas no signal could be detected in adult skeletal muscle. In regenerating muscle, HGF mRNA was reexpressed, and a distinct signal was evident during the first days after the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
76
1
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(83 citation statements)
references
References 14 publications
4
76
1
2
Order By: Relevance
“…Previous studies have reported that HGF is present in the extracellular matrix s u r r o u n d i n g m u s c l e f i b e r s 1 6 , 4 8 ) , o r immunolocalized at regenerating skeletal muscle 49) . In situ hybridization has also revealed HGF mRNA in regenerating muscle fibers 15,31) . In the present study, HGF was clearly immunolocalized in the cytoplasm of satellite cells early in the recovery process, strongly suggesting that HGF is produced by local satellite cells in response to reloading stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that HGF is present in the extracellular matrix s u r r o u n d i n g m u s c l e f i b e r s 1 6 , 4 8 ) , o r immunolocalized at regenerating skeletal muscle 49) . In situ hybridization has also revealed HGF mRNA in regenerating muscle fibers 15,31) . In the present study, HGF was clearly immunolocalized in the cytoplasm of satellite cells early in the recovery process, strongly suggesting that HGF is produced by local satellite cells in response to reloading stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the proliferation of satellite cells is stimulated by growth factors such as hepatocyte growth factor (HGF) 15,16) , insulin-like growth factors [17][18][19] , fibroblast growth factors 20,21) , transforming growth factor β 10) , platelet-derived growth factor BB 10,14) , and epidermal growth factor 17,18) . However, only HGF has been shown to cause satellite cells to exit the G 0 phase and enter the G 1 phase in vitro 22,23) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 HGF mRNA and protein can be down-regulated by hypoxia, 39 although this may be a time-and tissue-dependent phenomenon. 15,40 In patients as well as in a myocardial ischemia model, c-met is up-regulated in response to hypoxia. 40 -42 Down-regulation of HGF in response to hypoxia may be an important contributor to the pathology associated with peripheral vascular disease, and the up-regulation of c-met in peripheral vascular disease may offer an opportunity for therapeutic intervention with HGF.…”
Section: Discussionmentioning
confidence: 99%
“…7). Increasing evidence has shown that HGF is a multifunctional polypeptide with actions on a wide variety of cell types, including microglia (8), skeletal muscle (9), Schwann cells (10), and central nervous system neurons (11)(12)(13).…”
mentioning
confidence: 99%